"Girl Math, Boy Math": The Presence of Toxic Masculinity in TikTok and X Jargon - Salma, Haniyatuz Zaidah; Leiliyanti, Eva (KnE Social Sciences, 2024)
Jargon or slang words have become a norm in everyday online discourses and conversations, with a recent emergence of gendered terminology classifying activities and fashion aesthetics into a type of “girl” or “boy”, both heavily popularized thanks to social media. A notable example is seen in the recent rise of gendered-specific jokes called “girl math”, which is a comedy created by women on the justification of impulse shopping. This phenomenon began to give way to its counterpart called “boy math”. Initially, mockery on male behavior began to expand into the areas of critiquing toxic masculinity and misogyny in society as a whole. Through sampling data from accounts that receive high traction from using such terms on the platforms of X and TikTok, the researcher is interested in conducting an intertextual research using the framework of appraisal and feminist theory in order to elucidate the linguistic nuances and cultural influences stored within these gender-specific terms, ultimately unveiling how they critique male hegemony. This research is hoped to contribute to furthering the understanding of how technology, social media, and language intersect, shaping both learning environments and societal perceptions of gender roles. Keywords: X, TikTok, appraisal theory, language evaluation, misogyny, toxic masculinity